Methodology for ensuring employee engagement in the context of enterprise digital transformation - I. V. Kablashova; I. V. Logunova; V. N. Rodionova (Вестник университета)
The implementation of strategic priorities of domestic enterprises digital transformation actualizes the tasks of employee engagement in this process. It necessitates the development of methodological approaches to the study of employee engagement in strategic decision-making to improve the quality of processes and production activities of the enterprise. The purpose of the study is to present the results of research on methodological approaches development that reveal the content and features of employee engagement management in the activities of the enterprise. The research methodology includes logical substantiation of essence of the processes under study, data from scientific and analytical publications on the problem under consideration. In the course of the research interrelation between the problems of ensuring employee engagement and leadership of enterprise management has been revealed, and criteria for evaluating the actions of different categories of personnel in ensuring and increasing employee engagement developed. Active and passive approaches to involvement management determining interests of managers and employees and their influence on business results and organizational changes have been identified. The model of employee engagement in enterprise’s activities has been created considering the content of digital transformation processes, application of which allows motivating personnel to manifest digital initiatives and participate in the activities of project teams. The conclusions obtained by the authors are of a theoretical and applied nature. They will contribute to development of scientifically based approaches to developing a strategy for managing employee engagement in digital transformation processes. The results of the research can be useful to scientists and practitioners dealing with the problems of human resource management in innovations and digital standards of industrial enterprises implementation.